Estimating the cost of training disruptions on marathon performance - Feely, Ciara; Smyth, Barry; Caulfield, Brian; Lawlor, Aonghus (Frontiers in Sports and Active Living, 2023)
Completing a marathon usually requires at least 12-16 weeks of consistent training, but busy lifestyles, illness or injury, and motivational issues can all conspire to disrupt training. This study aims to investigate the frequency and performance cost of training disruptions, especially among recreational runners. Methods: Using more than 15 million activities, from 300,000 recreational runners who completed marathons during 2014-2017, we identified periods of varying durations up to 16 weeks before the marathon where runners experienced a complete cessation of training. We identified runners who had completed multiple marathons including: (i) at least one disrupted marathon with a long training disruption of >=7 days; and (ii) at least one undisrupted marathon with no training disruptions. Next, we calculated the performance cost of long training disruptions as the percentage difference between these disrupted and undisrupted marathon times, comparing the frequency and cost of training disruptions according to the sex, age, and ability of runner, and whether the disruptions occured early or late in training. Results: Over 50% of runners experienced short training disruptions up to and including 6 days, but longer disruptions were found to be increasingly less frequent among those who made it to race-day. Runners who experience longer training disruptions >=7 days suffer a finish-time cost of 5-8% compared to when the same runners experienced only short training disruptions <7 days. While we found little difference (<5%) in the likelihood of disruptions - when comparing runners based on sex, age, ability, and the timing of a disruption -- we did find significant differences in the the cost of disruptions (10-15%) among these groups. Two sample t-tests indicate that long training disruptions lead to a greater finish-time cost for males (5%) than females (3.5%). Faster runners also experience a greater finish-time cost (5.4%) than slower runners (2.6%). And, when disruptions occur late in training (close to race-day), they are associated with a greater finish-time cost (5.2%) than similar disruptions occurring earlier in training (4.4%). Conclusion: By parameterising the cost of training disruptions, this work can help runners and coaches to better understand the relationship between training consistency and marathon performance.